2013
DOI: 10.1038/jp.2013.43
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficacy of an intervention to reduce secondhand smoke exposure among infants discharged from a neonatal intensive care unit

Abstract: A need for SHSe interventions among NICU parents exists and initial evidence suggests MI can impact SHSe after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 22 publications
1
64
0
Order By: Relevance
“…Our findings inform targeted trials to reduce SHS exposure among children, especially those with illnesses, who live in homes of hookah smokers (Stotts et al, 2011(Stotts et al, , 2013Tyc et al, 2012). Such trials are important in the context of the studies successfully completed in the last 20 years showing that SHS exposure can be reduced when families are coached to do so (Hovell et al, 1994(Hovell et al, , 2000(Hovell et al, , 2002(Hovell et al, , 2009Klepeis et al, 2013;Meltzer, Hovell, Meltzer, Atkins, & de Peyster, 1993).…”
Section: Continuedmentioning
confidence: 93%
“…Our findings inform targeted trials to reduce SHS exposure among children, especially those with illnesses, who live in homes of hookah smokers (Stotts et al, 2011(Stotts et al, , 2013Tyc et al, 2012). Such trials are important in the context of the studies successfully completed in the last 20 years showing that SHS exposure can be reduced when families are coached to do so (Hovell et al, 1994(Hovell et al, , 2000(Hovell et al, , 2002(Hovell et al, , 2009Klepeis et al, 2013;Meltzer, Hovell, Meltzer, Atkins, & de Peyster, 1993).…”
Section: Continuedmentioning
confidence: 93%
“…[20][21][22][23][24][25]28,29,[31][32][33]84,85,88,90,91,93,96 One study did not report the number of sessions. 34 …”
Section: Intervention Intensitymentioning
confidence: 99%
“…21,28,29,32,[85][86][87]90,[92][93][94]96 Fidelity Seven studies reported high fidelity, with at least 80% of participants receiving the full intervention 23,24,27,84,88,93,96 ; 6 studies had moderate fidelity, with 50% to 79% of participants receiving the intervention 25,[29][30][31][32][33] ; and the remaining 17 studies did not report fidelity. [20][21][22]26,28,34,83,[85][86][87][89][90][91][92]94,95,97 Intervention Effects…”
Section: Rosen Et Almentioning
confidence: 99%
See 2 more Smart Citations